Replacement Versus Expansion: Dilemma for Mature U.S. Businesses - MacMillan, I. C.; Meshulach, A. (Academy of Management Journal, 1983)
Patterns of investment in expansion and/or replacement of equipment by strategic business units of U.S. companies in the PIMS data base were analyzed, using a hierarchical framework that assumes that investment decisions are made at two levels: the business level and the corporate level. Strong empirical support was found for the postulated hierarchical framework.